The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1128/jcm.01847-18
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Detection of Tuberculosis by Oral Swab Analysis

Abstract: Diagnostic tests for tuberculosis (TB) usually require collection of sputum, a viscous material derived from human airways. Sputum can be difficult and hazardous to collect and challenging to process in the laboratory. Oral swabs have been proposed as alternative sample types that are noninvasive and easy to collect. This study evaluated the biological feasibility of oral swab analysis (OSA) for the diagnosis of TB. Swabs were tested from South African adult subjects, including sputum GeneXpert MTB/RIF (GeneXp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
133
3
3

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(157 citation statements)
references
References 26 publications
6
133
3
3
Order By: Relevance
“…Similarly, saliva collected from the tongue has also held promise. In a two-phase study, tongue swabs (two per subject) exhibited a combined sensitivity of 92.8% relative to sputum for tuberculosis detection in adults 12 , and exhibited promise as non-invasive samples for diagnosis of pediatric tuberculosis 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, saliva collected from the tongue has also held promise. In a two-phase study, tongue swabs (two per subject) exhibited a combined sensitivity of 92.8% relative to sputum for tuberculosis detection in adults 12 , and exhibited promise as non-invasive samples for diagnosis of pediatric tuberculosis 13 .…”
Section: Discussionmentioning
confidence: 99%
“…These results support the possible utility of oral swab samples for TB detection. Luabeya et al reported that Omniswab tongue swabs yielded significant better results compared to cheek swabs, with a sensitivity of 71.2% for a single swab and 83.1% for two swabs in 59 patients (case definition based on Xpert or liquid culture) and 83.1% for single swab in another group of 89 patients (compared to Xpert MTB/RIF) (2). Their additional use of sputum Xpert as the reference test and tongue swab may in part explain the higher observed sensitivity in their study and would be interesting adjustments to the Xpert protocol.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were randomly assigned to one of three sample collection groups to assess collection methods and storage procedures: 1. Omniswab (Whatman, catalog #WB100035) in lysis buffer as described in (1,2); 2. Omniswab in phosphate buffered saline (PBS); 3.…”
Section: Methodsmentioning
confidence: 99%
“…DNA was extracted from the swab samples by using a modified Qiagen protocol described previously 10,11 . Quantitative PCR targeting IS6110, a multi-copy insertion element unique to the M. tuberculosis complex, was done as described 11 . DNA extraction and qPCR were conducted in a 3-room laboratory suite with one-way workflow to minimize sample contamination.…”
Section: Methodsmentioning
confidence: 99%
“…One of the simplest samples to obtain is a swab of the oral mucosa 7 . Originally demonstrated for diagnosis of TB in non-human primates 8,9 , we have shown that oral swab PCR could detect approximately 90% of microbiologically confirmed cases of pulmonary TB in adults 10,11 . As potential samples for pulmonary TB testing in young children, oral swabs (OS) have the advantage of being universally obtainable with minimal discomfort or need for operator training.…”
mentioning
confidence: 99%